2019
DOI: 10.1021/acs.jpcc.9b03240
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potentials of Metal–Organic Frameworks as Adsorbents and Membranes for Separation of Hexane Isomers

Abstract: Molecular modelling and computational science tools were employed to select a number of metal−organic frameworks (MOFs) from a pool of 4764 structures to investigate and assess their kinetic and adsorption-based separation performances in separating hexane isomers. The self-diffusivities of all single-component isomers were obtained from molecular dynamics simulations at infinite dilution and at a loading of 4 molecules/unit cell and at several temperatures. The self-diffusivities of the binary mixtures of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…Comparing with the profiles of n -hexane (Figure ), we can see that the energy barriers for propane are indeed lower than for n -hexane by about 10 kJ/mol, while the locations of the barriers and wells remain the same, which supports our argument. Similar correlations between barrier heights and diffusivities have also been observed in a recent high-throughput screening study on the diffusion of different hexane isomers in a database of MOFs …”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Comparing with the profiles of n -hexane (Figure ), we can see that the energy barriers for propane are indeed lower than for n -hexane by about 10 kJ/mol, while the locations of the barriers and wells remain the same, which supports our argument. Similar correlations between barrier heights and diffusivities have also been observed in a recent high-throughput screening study on the diffusion of different hexane isomers in a database of MOFs …”
Section: Resultssupporting
confidence: 80%
“…Similar correlations between barrier heights and diffusivities have also been observed in a recent high-throughput screening study on the diffusion of different hexane isomers in a database of MOFs. 55…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Recently, Solanki and Borah screened 4764 MOFs from the Computational Ready Experimental (CoRE) MOF database for separation of hexane isomers, and picked 11 of the most promising MOFs for more detailed pure component diffusivity simulations at infinite dilution to determine kinetic selectivity coefficients [204]. Solanki and Borah found that, among the different MOFs examined, the diffusivities of hexane isomers varied by more than an order of magnitude, indicating large kinetic selectivity to specific isomers.…”
Section: Multicomponent Diffusion In Metal-organic Frameworkmentioning
confidence: 99%
“…The segregation of the MOFs on the basis of hierarchy of adsorption of the hexane isomers is necessary in order to tune the membrane selectivity. In a recent work, we have observed that MOFs that show a normal hierarchy of adsorption are more selective toward the branched alkanes kinetically and vice versa . This leads to low membrane selectivity.…”
Section: Molecular Modeling and Computational Detailsmentioning
confidence: 99%
“…In a recent work, we have observed that MOFs that show a normal hierarchy of adsorption are more selective toward the branched alkanes kinetically and vice versa. 38 This leads to low membrane selectivity. Therefore, the segregation of the MOFs to these two categories of normal hierarchy and reverse hierarchy of adsorption followed by close observation of their structural properties might lead us to a way of tuning the membrane selectivity to a maximum value.…”
Section: ■ Introductionmentioning
confidence: 99%